Transactions on Data Hiding and Multimedia Security IX Special Issue on Visual Cryptography - Shi, Yun Q.; Liu, Feng.; Yan, Weiqi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Since the mid 1990s, data hiding has been proposed as an enabling technology for securing multimedia communication and is now used in various applications including broadcast monitoring, movie fingerprinting, steganography, video indexing and retrieval and image authentication. Data hiding and cryptographic techniques are often combined to complement each other, thus triggering the development of a new research field of multimedia security. Besides, two related disciplines, steganalysis and data forensics, are increasingly attracting researchers and becoming another new research field of multimedia security. This journal, LNCS Transactions on Data Hiding and Multimedia Security, aims to be a forum for all researchers in these emerging fields, publishing both original and archival research results. The seven papers included in this special issue were carefully reviewed and selected from 21 submissions. They address the challenges faced by the emerging area of visual cryptography and provide the readers with an overview of the state of the art in this field of research.
ESSVCS: An Enriched Secret Sharing Visual Cryptography -- Extended Visual Cryptography Scheme for Multiple-Secrets Continuous-Tone Images -- Ideal Secure Multi-Secret Visual Cryptography Scheme with Ring Shares -- Password Protected Visual Cryptography via Cellular Automaton Rule 30 -- A Novel Perceptual Secret Sharing Scheme -- Visual Cryptography Based Watermarking -- Flexible Visual Cryptography Scheme and Its Application.
Keywords: Cryptography; Data encryption (Computer science).; Data protection; Coding theory; Information theory; Computer vision; Cryptology; Data and Information Security; Coding and Information Theory; Computer Vision